2017
DOI: 10.1186/s12870-017-1060-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential proteomic analysis of replanted Rehmannia glutinosa roots by iTRAQ reveals molecular mechanisms for formation of replant disease

Abstract: BackgroundThe normal growth of Rehmannia glutinosa, a widely used medicinal plant in China, is severely disturbed by replant disease. The formation of replant disease commonly involves interactions among plants, allelochemicals and microbes; however, these relationships remain largely unclear. As a result, no effective measures are currently available to treat replant disease.ResultsIn this study, an integrated R. glutinosa transcriptome was constructed, from which an R. glutinosa protein library was obtained.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 103 publications
2
31
0
Order By: Relevance
“…Li et al initially obtained 94,544 and 99,708 unigenes from leaf and root transcript libraries, respectively [40]. They then collected 10 root samples from SP (five stages) and FP (five stages) and mixed them together to construct a root transcriptome library, collected 10 leaf samples to construct a leaf transcriptome library, and obtained 71,922 and 54,722 unigenes from the mixed root and mixed leaf libraries via the Illumina HiSeq ™ 2500 system, respectively [43]. Sun et al generated a total of 81,003 unique sequences from the cDNA library constructed from the ARs, TARs, and DTRs of R. glutinosa by using the Illumina sequencing platform [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al initially obtained 94,544 and 99,708 unigenes from leaf and root transcript libraries, respectively [40]. They then collected 10 root samples from SP (five stages) and FP (five stages) and mixed them together to construct a root transcriptome library, collected 10 leaf samples to construct a leaf transcriptome library, and obtained 71,922 and 54,722 unigenes from the mixed root and mixed leaf libraries via the Illumina HiSeq ™ 2500 system, respectively [43]. Sun et al generated a total of 81,003 unique sequences from the cDNA library constructed from the ARs, TARs, and DTRs of R. glutinosa by using the Illumina sequencing platform [41].…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al generated a total of 81,003 unique sequences from the cDNA library constructed from the ARs, TARs, and DTRs of R. glutinosa by using the Illumina sequencing platform [41]. In this study, we obtained 38,678~54,378 unigenes from the 24 cDNA libraries of radial striations and non-radial striations of R. glutinosa tuberous roots and eventually assembled a final set of 150,405 entries with an average length of 1244 bp higher than mixed roots unigenes (383 bp and 678 bp) [17,41] and mixed leaf and root unigenes (868 bp) [43]. This novel unigene database provides a high-quality reference transcriptome on gene expression detection and molecular mechanisms for R. glutinosa .…”
Section: Discussionmentioning
confidence: 99%
“…However, these inferences need to be further verified. Previous studies displayed that some plant hormones including ET and ABA involved in the formation mechanism of R. glutinosa replant disease and closely related to immune resistance [48,69]. Some studies have demonstrated that SA was involved in the defense against Fusarium oxysporum and associated with acteoside accumulation, one of the important pharmacodynamic component [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described that SA was involved in the defense against Fusarium oxysporum and associated with acteoside accumulation, one of important pharmacodynamic component [46,47]. Our recent study displayed that plant hormones involved in the formation mechanism of R. glutinosa replant disease and are closely related to immune resistance [48]. However, a comprehensive survey on the relationship between plant hormones and replant disease in R. glutinosa is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Bupleurum saikosaponin have certain regulatory effects on specific immune function and nonspecific immune function of the body. Rehmannia glutinosa [ 15 ] can significantly enhance the production of interleukin-2 (IL-2) in active lymphocytes and enhance the immune function. Chinses Angelica can promote the expression of IL-2, tumor necrosis factor γ, and other cytokines.…”
Section: Introductionmentioning
confidence: 99%